SUSTAINABLE ENTREPRENEURSHIP AND PROFITABILITY OF MANUFACTURING FIRMS IN ANAMBRA STATE - Chinelo Patience Ohanyere; Nnebe Ekwutosi Gloria; Chioma Francisca Okeke; Obinna Solomon Eboh (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The study analyzed the sustainable entrepreneurship and profitability of Manufacturing firms in Anambra State.  The objectives of the study were to:  determine the effect of economic impact on profitability of Manufacturing firms in Anambra State; determine the effect of environmental impact on profitability of Manufacturing firms in Anambra State; determine the effect of social impact on profitability of Manufacturing firms in Anambra State. Three research hypotheses were formulated in line with the above objectives of the study. Descriptive survey design method was used; the sample techniques employed in this study was simple random sampling. The population for this research work was two thousand six hundred and thirty-one (2631)., respondents. It comprises of all the staff working in the selected Manufacturing firms in Anambra State, while the sample size is 399 through Taro yamane formula. The researcher distributes three hundred and ninety-nine (399) questionnaires but only three hundred and seventy-two (372) copies of questionnaire were retrieved. Structured questionnaire were use to gather information from the population. Regression analysis and ANOVA method of data analysis was used to test the questionnaire. The finding of the study shows that; Economic Impact has significant positive effect on profitability of Manufacturing firm in Anambra State; Environmental impact has significant positive effect on profitability of Manufacturing firm in Anambra State; Social Impact has significant positive effect on profitability of Manufacturing firm in Anambra State. The study recommends Collaboration with governments and other organizations to develop and implement sustainable practices that benefit both the environment and the economy. Implement practices that reduce carbon emissions, such as using renewable energy sources, reducing energy consumption, and improving energy efficiency. Invest in social entrepreneurship projects that address social issues such as poverty, inequality, and environmental degradation.